Chemical characterization and evaluation of the antifungal activity of the Lippia alba essential oil against Colletotrichum gloeosporioides - Pérez Cordero, Alexander (2017)
The aim of this study was to characterize and evaluate the in vitro efficiency of leaf essential oil of Lippia alba against Colletotrichum gloeosporioides. Essential oil from the leaves was extracted by the method of assisted microwave hydrodistillation (MWHD) and metabolites were identified by gas chromatography coupled to mass spectrometry (GC/MS). The in vitro evaluation was performed using 4 concentrations of essential oil (500, 1000, 3000 and 10000 ppm) diluted in acetone; positive control with Benomyl 1 g /L, a negative control with acetone and absolute control was used; oil efficiency was measured by the percentage of antifungal index (% IA). It was found that the major component was in the essential oil citral (34.62 to 40.03%) and the highest %I.A was found to 10000 ppm concentration (97.8%) very similar to Benomyl (100%). This would demonstrate the efficacy of the L. alba essential oil to control C. gloeosporioides, and its possible use as a biological fungicide.